Manuales de urbanidad y discursos sobre el ornato en Cuba en el siglo XIX: Hacia un gobierno de los sentidos, el cuerpo y la ciudad. - Egüez Guevara, Pilar (Latin American Research Review, 2018)
Books of etiquette emerged in Cuba during the nineteenth century as a tool that the creole class used to impose themselves as the model of an imagined national subject. Also known as manuals of urbanity and good manners, these texts projected the aspirations of the creole elite. They served as technologies to craft a kind of body-bourgeois, white, heterosexual, Cuban- molded to inhabit the new urban spatial configurations that the modernizing tendencies of the early century brought forth. I examine the synergistic ways in which manuals of conduct and their driving ideology, urbanity, developed in close relationship with the ornate-another major technology of government and differentiation of bodies through space. Politics of the ornate aimed to transform Havana into an elegant capital which was modern and colonial at once, and make its image “decent,” that is, clean from sensory references to black and female marginal bodies. I examine the discursive connections between the ornate and urbanity to unpack how modern bourgeois respectability was negotiated in a symbolic realm and through the regulation of sensations and emotions.